Experimental and Theoretical 15N NMR and 1JCH Spin-Spin Coupling Constants Investigation of 1-Phenylpiperazine - Özgür Alver; Cemal Parlak (Süleyman Demirel Üniversitesi Fen-Edebiyat Fakültesi Fen Dergisi, 2010)
Abstract: The magnitude of one bond 1JCH coupling constants, proton coupled 13C NMR and 15N NMR spectra for 1-Phenylpiperazine (pp) have been reported for the first time. 15N NMR chemical shifts and 1JCH coupling constants of pp (C10H14N2) have been calculated by means of the Becke-3-Lee-Yang-Parr (B3LYP) density functional method with the 6-311++G(d,p) basis set. Comparison between the experimental and theoretical results indicates that DFT/B3LYP method is in good agreement with the experimental data for predicting NMR properties.